Analysis of Tax Innovation Breakthrough on E-Bphtb System to Minimize Fraud in the Local Revenue Office of Samarinda - Kristin Wulansari; Della Olivia Caterina Kalangit; Sailawati Sailawati (Publikasi Indonesia, 2022)
The COVID-19 pandemic is a massive health calamity that will also result in an impending global economic restructuring. The impact of COVID-19 Pandemic is extensive and has presented enormous challenges to the world as a whole. A full economic recovery from the COVID-19 is unlikely. The governments must building resilience and leading in this time of crisis to a new phase new normal in the COVID-19 pandemic. Online service (e-Government) is a solution but the challenge in the success of online service (e-Government) implementation. The purpose of this research is to define the processes, challenges and opportunities for the application of the e-BPHTB systems in the Regional Revenue Office of Samarinda. A qualitative descriptive methodology is used in this research. The results of this research suggest that the e-BPHTB system implementation has been successful. Investment in e-BPHTB systems enhances performance, efficacy and quality of service in The Local Revenue Agency of Samarinda. The result also showed that the challenges of e-BPHTB implementation, such as : the quality infrastructure system, the complicated of regional regulations, and the taxpayer’s awareness so bad.